The Clinical Link of Preschoolers’ Picky Eating Behavior with Their Growth, Development, Nutritional Status, and Physical Activity in Iraq/Kurdistan Region - Khajik Sirob Yaqob Qazaryan; Saad Kazim Karim (Highlights on Medicine and Medical Science Vol. 5, 2021)
Background: This study aimed to evaluate the prevalence of picky eating among preschoolers and to estimate the clinical association between eating behaviour and growth, physical activity, development, and health status. Aims: The goal of this research study is to identify and find out the clinical impacts of picky eating behaviour on preschoolers and children aged schools in terms of their physical growth, neurodevelopment, nutrition and physical activity. Methods: In this study, a structured questionnaire was used to perform a cross-sectional descriptive study of 800 parents of preschoolers aged 2–4 years in Kurdistan/Iraq. Data collected included: demographics, food preferences, eating behaviour, body weight, BMI, height, development, physical activity, and records of medical illness. Data from children defined as picky or non-picky eaters responses were analyzed and compared using standard statistical tests according to the parental’ questionnaire. Results: The mean age of the children was 2.85 years; among 800 participants, 620 (77%) were picky eaters. Compared with non-picky eaters 180 (23%), z-score of weight-for-age, height-for-age, and body mass index (BMI)-for-age in picky eaters was 0.91, 0.73, and 0.44 SD lower, respectively. There were significant variations of rates in the weight-for-age, height-for-age, and BMI-for-age percentiles <15, between picky and non-picky eaters (P = 0.04, 0.023, and 0.005, respectively). Certain findings were higher in picky as compared to non-picky preschoolers including negative social communication such as afraid of unfamiliar places 65% vs 13.3%, afraid of being lonely 14.6% vs 12.1%, poor physical activity 36.8% vs 17.7%, learning disability 16.2% vs 7%, attention deficit 11.8% vs 4.3%, speech delay 4.6% vs 3.3%, respectively). Conclusion: The prevalence of picky eaters in preschool children was high, resulting in significant detrimental impacts on growth, nutritional status, development, physical activity and health status.